Proverb - An Artistic Publicist Genre - Zulxumor Radjabovna, Djurayeva; Luiza Ravshanovna, Sidorkova; Viktoriya Anatolevna, Gudzina; Djamila Xasanovna , Temirova; Marina Aleksandrovna, Bokareva (International Journal of Psychosocial Rehabilitation, 2020)
One of the factors that reflects the national values and culture of the nation is the oral culture of the people. One of the most important genres of folklore is that the proverbs are one of the most important subjects in linguistics and folklore. The study of proverbs, one of the most important genres of folklore, and the study of folklore in general, is very important today. This article aims to examine the common features of Uzbek and English proverbs and their similarities and differences in other genres of folklore.